Portal Vein Thrombosis Might Develop by COVID-19 Infection or Vaccination: A Systematic Review of Case-Report Studies - Kheyrandish, Setare; Rastgar, Amirhossein; Arab-Zozani, Morteza; Sarab, Gholamreza Anani (Frontiers in Medicine, 2021)
Background and objective: Infection by the novel coronavirus (COVID-19) has been associated with different types of thrombotic complications same as portal vein thrombosis (PVT). However, by emerging COVID vaccines, the thrombosis did not seem to be concerning any more. Until new findings showed that, the COVID vaccine itself can cause PVT. Method: We performed an electronic search in PubMed, Scopus, and Web of Sciences to evaluate the possibility of occurring PVT due to COVID-19 infection and vaccination. The results were reported in a narrative method and categorized into tables. Result: Of forty cases, it was shown that if PVT is resulted from COVID-19 infection, it is more prevalent in males. However, it is vice versa if it happens following COVID-19 vaccination. In total, 20 cases had at least one underlying disease. The most common clinical presentation was abdominal pain. After anticoagulant therapies, most of the patients improved or discharged. Conclusion: As long as the laboratory findings are not good enough to predict PVT, the diagnosis of this complication with whatever underlying reason is challengeable while rapid diagnosis and treatment of that is vital. Therefore, by providing available data in an organized way, we aimed to prepare the information of infected patients for better and easier future diagnosis of PVT in new cases.